The potential of bacterial biocontrols in managing finger millet blast disease and promoting growth: A review - Melkamu Andargie; Merkuz Abera; Tesfaye Alemu; Berhanu Bekele (The Microbe)
Finger millet plays a crucial role as a food crop in Ethiopia; however, its production is considerably threatened by blast disease caused by Magnaporthe grisea. Effective management of the disease is critical to reduce yield losses, and biological control has emerged as a promising alternative to traditional methods. This review examines the potential of biocontrol strategies in the management of finger millet blast while also promoting plant growth. Beneficial microorganisms, including bacterial species like Pseudomonas fluorescens and Bacillus subtilis, as well as fungal antagonists such as Trichoderma spp., have shown effectiveness in inhibiting Magnaporthe grisea through mechanisms like antibiosis, competition, parasitism, and the induction of systemic resistance. Moreover, these biocontrol agents support plant health by improving growth and resilience. To maximize their potential, more research is necessary to improve the use of biocontrol agents in various environments, including the application of genetically modified microorganisms for the production of secondary metabolites. It is essential to carry out molecular characterization, clarify the mechanisms of biocontrol, and identify the key genes associated with enzyme activity and the generation of bioactive compounds. Furthermore, investigations should focus on their impact on promoting plant growth. Attention must also be directed toward increasing production capacity and the commercialization of microbial biopesticides. Progress in these fields is crucial for the creation of sustainable and effective disease management strategies in finger millet farming.